Maulia Samsa Pengaruh Kualitas Produk, Harga dan Citra Merek Terhadap Keputusan Pembelian Pada Hajj Chicken Resto Pakisaji Malang - Maulia Samsa; Meylani Tuti (LPPM Universitas Asa Indonesia, 2022)
The purpose of this study was to determine whether product quality, price and brand image affect purchasing decisions. The population in this study were visitors to Hajj Chicken Resto Pakisaji Malang who had made purchases more than twice. The sample used in this study is purposive sampling using the number of respondents 120 people. The method used is quantitative research methods and uses multiple linear analysis techniques. The results of the study prove that there is an influence of product quality (X1), price (X2) and brand image (X3) on purchasing decisions (Y) fried chicken flour at Hajj Chicken Resto Pakisaji Malang partially and simultaneously.